Factors Influencing Students’ Interest in Becoming Baznas Amil - Viska, Wafiroh Wati Viskadani; Parwi, Suparwi (El-Barka, 2024)
This study aims to examine the factors influencing students’ interest in becoming BAZNAS Amil among the students of the Faculty of Islamic Economics and Business at IAIN Kudus. The sample consisted of 100 students selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression analysis with SPSS software version 26. The results show that, partially, labor market opportunities, social influence, and income have a positive and significant effect on the interest of students in the Faculty of Islamic Economics and Business at IAIN Kudus to become BAZNAS Amil. Conversely, motivation and religiosity do not have a significant partial effect on students’ interest. Simultaneously, labor market opportunities, social influence, income, motivation, and religiosity positively and significantly influence students’ interest in becoming BAZNAS Amil. This research contributes to zakat management by identifying factors that can enhance the interest of young generations, particularly students, in contributing as zakat administrators (Amil). The findings are expected to serve as a reference for BAZNAS in designing more effective recruitment strategies that align with the needs of the younger generation.